DOP076 IL-3 drives IL-10-secreting Tr1 cells to counteract experimental colitis. (16th January 2018) - Zundler, S; Spocinska, M; Popp, V; Becker, E; Atreya, R; Neufert, C; Atreya, I; Weigmann, B; Neurath, M F
Abstract: Background: T cells and T-cell-secreted cytokines play a central role in the pathogenesis of inflammatory bowel diseases. Although several reports have shown that IL-3 secreted by T cells has an important function in the pathogenesis of several immunologically mediated diseases like rheumatoid arthritis or lupus erythematodes, its potential contribution to IBD has not been investigated so far. Methods: The expression of IL-3 and IL-3 receptor (CD123) in the gut of control donors and patients with IBD was evaluated by qPCR and immunohistochemistry. Human peripheral blood CD4 + T cells were incubated with IL-3 in vitro and analysed by flow cytometry. IL-3 −/− (IL-3 KO) and IL-3 +/+ (WT) mice were studied in experimental colitis models. Results: The expression of IL-3 in the colon of patients with ulcerative colitis (UC) but not Crohn's disease (CD) was significantly increased compared with non-IBD controls and expression was clearly correlated to disease severity in UC. Similarly, CD123 expression was augmented in UC. IL-3 KO mice developed severer disease in the acute oxazolone colitis model closely resembling UC as determined by weight, mini-endoscopy, histology and in vivo imaging of reactive oxygen species. A similar phenotype was observed in mice treated with an anti-IL-3 antibody compared with isotype-treated animals. Moreover, transfer colitis was severer after transfer of cells from IL-3 KO donors to Rag-1 −/− recipients compared with WT donors. Further studies showed high expression of CD123 on human and mouse CD49b + LAG-3 + Tr1 cells and an induction of IL-10 secretion upon treatment of CD4 + T cells with IL-3. Several markers of regulatory Tr1 cells were downregulated in CD4 + T cells from IL-3 KO mice with oxazolone colitis compare with WT mice. Conclusions: Our data indicate that IL-3 promotes the secretion of the anti-inflammatory cytokine IL-10 by the regulatory Tr1 T cell subset and protects mice from experimental colitis. This supports an important role of IL-3 in the pathogenesis of IBD, especially UC, and might provide a novel future strategy for the treatment of colitis.